sistem persamaan linear tiga variabel metode determinan - Mayada Alismi (Jurnal Pustaka Cendekia Pendidikan, 2024)
Determinants are a subject that is included in Linear Algebra. Determinants are used to solve problems related to Linear Algebra, including finding matrix inverses, determining the characteristic equation of a problem in determining eigenvalues, and solving linear equations